2017
DOI: 10.4103/pm.pm_503_16
|View full text |Cite
|
Sign up to set email alerts
|

Screening of fruits of seven plants indicated for medicinal use in Iraq

Abstract: Introduction:Coumarins exert many biological effects in humans, animals, and plants, which make the evaluation of their biological activities and study of their role in ethnomedicine highly valued.Objectives:Here, we selected seven plants which have ethnopharmacological use as antimicrobial in Iraq and the aims were to quantify the two structural isomers bergapten and methoxsalen in their seeds, to evaluate the antibacterial activities against several clinical isolates, and to isolate bergapten and methoxsalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The minimum inhibitory concentrations (MICs) of the plant extracts and compounds explored in this study were determined using the microplate Alamar Blue assay as previously described [32, 33]. The bacterial isolates were first adjusted to McFarland standard 0.5 (~ 1 × 10 8 CFU/ml), which were then diluted by adding 0.2 ml bacterial suspension to 19.8 ml sterile broth medium (1:100 fold dilution) to give the final bacterial concentration (1× 10 6 CFU/ml).…”
Section: Methodsmentioning
confidence: 99%
“…The minimum inhibitory concentrations (MICs) of the plant extracts and compounds explored in this study were determined using the microplate Alamar Blue assay as previously described [32, 33]. The bacterial isolates were first adjusted to McFarland standard 0.5 (~ 1 × 10 8 CFU/ml), which were then diluted by adding 0.2 ml bacterial suspension to 19.8 ml sterile broth medium (1:100 fold dilution) to give the final bacterial concentration (1× 10 6 CFU/ml).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that bergapten isolated from Heracleum maximum and it was inferred that the OCH 3 group at the C5 site in bergapten might be the functional site of antibacterial activity (Golfakhrabadi et al, 2016). Furthermore, bergapten was found to possess stronger antibacterial activity against Gram-positive bacteria than Gramnegative bacteria (Aldulaimi, 2017). Moreover, bergapten also showed a strong inhibitory effect on Colletotrichum sp., inhibiting its radial growth and spore germination (Ramirez-Pelayo, Martinez-Quinones, showed an inhibitory effect on aldose reductase (AR), which plays an important role in the pathogenesis of diabetic complications, and its IC 50 was 25.03 μM (Park, 2011).…”
Section: The Antimicrobial Activity Of Bergaptenmentioning
confidence: 99%
“…Moreover, bergapten isolated from Ferulago carduchorum could effectively inhibit Candida albicans (MIC = 0.23 mg/mL) but show poor inhibition of Staphylococcus aureus (MIC = 1.87 mg/mL), and it was inferred that the OCH 3 group at the C5 site in bergapten might be the functional site of antibacterial activity (Golfakhrabadi et al, 2016). Furthermore, bergapten was found to possess stronger antibacterial activity against Gram‐positive bacteria than Gram‐negative bacteria (Aldulaimi, 2017). Moreover, bergapten also showed a strong inhibitory effect on Colletotrichum sp., inhibiting its radial growth and spore germination (Ramirez‐Pelayo, Martinez‐Quinones, Gil, & Durango, 2019).…”
Section: Pharmacological Effects Of Bergaptenmentioning
confidence: 99%
“…Methoxsalen is a natural furocoumarin that can be obtained from several plant species, including Ammi majus, 29 Psoralea corylifolia 30 and Pastinaca sativa. 30,31,99,100 It is also known as xanthotoxin and is a pigmentation agent used in the treatment of psoriasis cutaneous, T-cell lymphoma, and vitiligo. [101][102][103] Methoxsalen is a potent inhibitor of CYP2A6 nicotine metabolism in the liver microsomes of adult male ICR mouse with a Ki of 0.32±0.03 µM.…”
Section: Methoxsalenmentioning
confidence: 99%